THE IMPACT OF EARLY INITIATION OF PHYSIOTHERAPY ON MOTOR RECOVERY IN ACUTE STROKE PATIENTS. - Uswa Ali Qazi1 , Sandhiya2 , Sadhna Bai3 , Haresh Kumar4 , Safdar Ali Pervaiz Tunio5 , Mir Tahir Hussain Talpur6 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT: BACKGROUND: The most common motor deficits that emerge from stroke have a major negative influence on sufferers' functioning abilities as well as their quality of life. Stroke is the main cause of disability globally. In order to encourage motor recovery and improve functional outcomes following a stroke, early beginning of physiotherapy is being advocated as a vital component of stroke care. The cross-sectional investigation sought to determine how early PT commencement affected acute stroke patients' motor improvement. METHOD: 200 patients with acute strokes in all were enrolled in the research from two tertiary institutions. Based on when physiotherapy was started, patients were split into two groups: those who began treatment right away (within a forty-eight hours of the stroke starting) and those who started later (after 48 hours). Using standardized outcome measures, such as the Fugl-Meyer Assessment (FMA) and the Action Research Arm Test (ARAT), motor recovery was evaluated. RESULTS: The outcomes of motor recovery were significantly correlated with when PT was started, according to the findings. Comparing the first start group to the postponed the group, the early initiation group showed better motor recovery. Participants in the early initiation group had higher FMA and ARAT scores than those in the delayed initiation group, respectively (p 0.001). Physiotherapy should be started as soon as possible in acute stroke patients, according to these findings, since this will promote motor recovery in the upper as well as the lower extremities. Subgroup analyses were also performed to find any relevant moderating variables. Age, the severity of the stroke, and the interval between the stroke and hospital admission were found to be important determinants of the association between early physiotherapy commencement and motor recovery outcomes. CONCLUSION: As a result, this cross-sectional study offers proof in favor of the beneficial effects of early physiotherapy commencement on motor recovery in patients with acute strokes. The results emphasize how critical it is to quickly incorporate PT treatments into the initial stage of stroke care. The significance of healthcare systems prioritizing early access to physiotherapy services for patients with acute strokes is highlighted by the possibility that early beginning of physiotherapy might help improve functional outcomes. To learn more about the long-term impacts and probable processes behind this connection, more longitudinal research are necessary.